Readmission for Morbidities among Postpartum Women in a Tertiary Hospital of Kathmandu - Ojha, Bijay; Pokharel, Sunil Mani; Silwal, Ajita (Journal of Karnali Academy of Health Sciences, 2023)
Background: Postpartum period is a critical stage where the majority of the maternal mortality occurs. Major obstetric morbidities during this period include postpartum haemorrhage, puerperal pyrexia, and sepsis, and pregnancy induced hypertension. The objective of this study was to find out the morbidities in postpartum women readmitted following discharge from the hospital after delivery.Methods: It was conducted as a hospital-based descriptive study at Paropakar Maternity and Women’s Hospital (PMWH), Thapathali, Kathmandu. Ethical clearance was obtained from Institutional Review Board (IRB) of National Academy of Medical Sciences (NAMS). The total population enumeration technique was used to collect the data for a period of three months. A Standard Performa containing socio demographic characteristics, causes of readmission, complications during pregnancy, time interval of readmission and outcome of readmission was prepared which include relevant points according to the objective of the study. Data analysis was done using the Statistical Package for Social Sciences 16. Descriptive statistics (frequency, percent, mean, standard deviation and range) were used to analyse the data.Results: The incidence of postpartum readmission was 1.0% of total deliveries with 58 women being readmitted. More than two-fifth (29, 43.9%) were readmitted due to abdominal and perineal wound infections followed by urinary tract infections (8, 12.1%). Hypertension, puerperal pyrexia, secondary postpartum haemorrhage were other conditions requiring readmission in postpartum period.Conclusion: The study concluded that the women were readmitted during their postpartum period for multiple causes, wound infection being the most common. The quality of postnatal care including proper examination before discharge is necessary to ensure reduction in the readmission rate.